2006
DOI: 10.1073/pnas.0606083103
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community in a sediment-hosted CO 2 lake of the southern Okinawa Trough hydrothermal system

Abstract: Increasing levels of CO2 in the atmosphere are expected to cause climatic change with negative effects on the earth's ecosystems and human society. Consequently, a variety of CO 2 disposal options are discussed, including injection into the deep ocean. Because the dissolution of CO2 in seawater will decrease ambient pH considerably, negative consequences for deep-water ecosystems have been predicted. Hence, ecosystems associated with natural CO2 reservoirs in the deep sea, and the dynamics of gaseous, liquid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
149
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(155 citation statements)
references
References 39 publications
5
149
0
1
Order By: Relevance
“…Venting of clear fluid with the highest temperature of 220 C was observed at the foot of the mound, which was accompanied with discharge of significant amount of liquid CO 2 droplets. Liquid CO 2 emanation from altered sediment has been observed in many places around the active hydrothermal mounds (Inagaki et al 2006;Konno et al 2006). In the southern part of the hydrothermal field (the Abyss Vent site), diffusive fluid venting was observed from the seafloor which is covered with sediment associated whitish hydrothermal crusts (Inagaki et al 2006).…”
Section: Daiyon-yonaguni Knoll Hydrothermal Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Venting of clear fluid with the highest temperature of 220 C was observed at the foot of the mound, which was accompanied with discharge of significant amount of liquid CO 2 droplets. Liquid CO 2 emanation from altered sediment has been observed in many places around the active hydrothermal mounds (Inagaki et al 2006;Konno et al 2006). In the southern part of the hydrothermal field (the Abyss Vent site), diffusive fluid venting was observed from the seafloor which is covered with sediment associated whitish hydrothermal crusts (Inagaki et al 2006).…”
Section: Daiyon-yonaguni Knoll Hydrothermal Fieldmentioning
confidence: 99%
“…Liquid CO 2 emanation from altered sediment has been observed in many places around the active hydrothermal mounds (Inagaki et al 2006;Konno et al 2006). In the southern part of the hydrothermal field (the Abyss Vent site), diffusive fluid venting was observed from the seafloor which is covered with sediment associated whitish hydrothermal crusts (Inagaki et al 2006). Further south, inactive or diffuse venting from small chimney structures has been recognized, although the area has not been well explored.…”
Section: Daiyon-yonaguni Knoll Hydrothermal Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Another six hydrothermal vent sites in the Okinawa Trough were found subsequently: CLAM (Gamo et al, 1991), MinamiEnsei (Chiba et al, 1993), Iheya North (Chiba et al, 1996;Nakagawa et al, 2005), Hatoma Knoll (Nakano et al, 2001), Yonaguni Knoll IV (Kishida et al, 2004;Konno et al, 2006;Inagaki et al, 2006;Hongo et al, 2007;Suzuki et al, 2008;Nunoura and Takai, 2009), and HAKUREI (Ishibashi et al, 2009). A notable geological Suzuki et al, 2008). origin of the excess methane at sediment-related hydrothermal system was explained by methane production through thermal decomposition of sedimentary organic matter (e.g., Ishibashi et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The candidate phylum OP5 was represented originally by environmental clone sequences retrieved from the Obsidian Pool in Yellowstone National Park (Hugenholtz et al, 1998a) and indicated an independent phylum-level lineage in the domain Bacteria (Hugenholtz et al, 1998a, b;Rappé & Giovannoni, 2003). Since then, environmental clone sequences belonging to this phylum have been detected in various environments (Dojka et al, 1998;Humayoun et al, 2003;Inagaki et al, 2006;Kaksonen et al, 2004;Ley et al, 2006;Skirnisdottir et al, 2000;Teske et al, 2002). Strain AZM16c01 T was the first cultivable isolate accommodated in OP5.…”
mentioning
confidence: 99%